Characterization of Surface Level Wind in the Centro de Lançamento de Alcântara for Use in Rocket Structure Loading and Dispersion Studies - Marciotto,Edson R. (2012)
Abstract: We present wind data collected for ten days during the dry season in 2008 during the Murici II Campaign, which was carried out in the area of the Centro de Lançamento de Alcântara (CLA). The main goals are to better understand processes governing the wind regime in the CLA and the development of tools for analyzing the impact of wind on rocket structure and on the dispersion of pollutants released during the launch. A set of 11 aerovanes (ten at 10-m heightandone at 1.5-m height) plus a sonic anemometer at 1.5-m heightwere deployed to measure Wind speed and direction, which were stored as ten-minute data. Turbulence intensity, gust factor, and gust amplitude were computed from the available dataset. Statistical analysis shows that the wind direction is predominant from East-Northeast (ENE), with the mean vector wind direction of 60º, in agreement with the trade wind regime. The diurnal cycle of ali statistical properties ofthe wind are strongly marked. Wind speed, turbulence intensity, and gusts are peaked at about 1000 LST. The presence of a non-diurnal cycle off our days has been noticed and might be associated with synoptic systems acting on the region. A simple heuristic formula was proposed to compute Lagrangian time-scalefrom Eulerian time-scale, and from which we compute the Lagragian standard deviation, afinal product to be used as input in diffusion models.